Understanding blood clot mechanical stability: the role of factor XIIIa-mediated fibrin crosslinking in rupture resistance - Ranjini K. Ramanujam; Yona Lavi; Lauren G. Poole; John L. Bassani; Valerie Tutwiler (Research and Practice in Thrombosis and Haemostasis)
Background: Embolization, or rupture of a thrombus, is a complication of thrombosis that increases mortality risk by up to 30%. Fibrin provides mechanical and structural stability to blood clots. Activated factor (F)XIIIa (FXIIIa), a transglutaminase, catalyzes the formation of isopeptide bonds between fibrin fibers and is a crucial regulator of the mechanical properties of clots. FXIIIa deficiency is associated with an increased risk of bleeding and embolization. Although the mechanical response of clots is known to be influenced by fibrin crosslinking, its specific implications for the clinical outcomes of embolization remain unclear. Objectives: Here, we characterized the influence of fibrin crosslinking on mechanical toughness (rupture resistance). Methods: The extent of crosslinking was altered using iodoacetamide, which inhibits the activity of FXIIIa. Single-edge notch fracture tests were performed to examine fibrin strength, extensibility, and toughness under a constant strain rate. Viscoelastic mechanics was assessed using rheology. Confocal and scanning electron microscopy were utilized to quantify the fibrin network structure as a function of fibrin crosslinking. Results: Our results revealed that increasing iodoacetamide concentration (0-0.1 mM) decreased toughness (8.6-2.3 N/m; P < .01) and the maximum force prior to rupture (0.09-0.06 N; P < .01), and the extensibility of the macroscale network remained unaltered (P > .05), indicating that fibrin crosslinking toughens the clot. As anticipated, inhibition of fibrin crosslinking resulted in reduced storage modulus (stiffness) of clots (50-11 Pa; P < .0001). Although inhibition of FXIIIa crosslinking altered the fibrin structure by reducing fibrin density and fiber length, these changes were not pronounced. Conclusion: These findings reveal a significant contribution of fibrin crosslinking to the fracture toughness of fibrin clots, suggesting a role in the propensity for embolization.